Analysis of Institut Teknologi Bandung Students Satisfaction Level Towards Dimsum House - Hafizh, Raiza Azkaril; Hartati, Sri (Journal of Business and Management, 2019)
"The increasing number of culinary restaurants in Bandung city is inseparable from the high interest of the public and tourists for the varied and innovative culinary needs, that lead to increase of competition between restaurants. This study specifically investigates dimsum business in Bandung city, and takes the Dimsum House restaurant as the main sample. Dimsum House facing a lot of competitors in that is spread in their current selling location. Therefore, for restaurants to win in the current competition, an analysis of customer satisfaction is needed to compete. Customer satisfaction is predicted to have four main determinants such as product quality, price, service quality, and easiness. The scope of customer is reduced to Institut Teknologi Bandung student as the main source of customers. The data of this study used quantitative and primary data from 305 respondents and measured by multi linear regression. The results show that only product quality is the main influences factor to customer satisfaction. Therefore, business owner and entrepreneurs are advised to focus on improving and fixing their product quality rather than price, service quality, and easiness.Keywords: Customer satisfaction, Product quality, Price, Service quality, Easiness, Business competition"